AFFINE HYPERSPHERES ASSOCIATED TO SPECIAL PARA-KÄHLER MANIFOLDS - CORTÉS,V; LAWN,M-A; SCHÄFER,L (International Journal of Geometric Methods in Modern Physics, 2006)
We prove that any special para-Kähler manifold is intrinsically an improper affine hypersphere. As a corollary, any para-holomorphic function F of n para-complex variables satisfying a non-degeneracy condition defines an improper affine hypersphere, which is the graph of a real function f of 2n variables. We give an explicit formula for the function f in terms of the para-holomorphic function F. Necessary and sufficient conditions for an affine hypersphere to admit the structure of a special para-Kähler manifold are given. Finally, it is shown that conical special para-Kähler manifolds are foliated by proper affine hyperspheres of constant mean curvature.